Study on Plastic Zone Distribution Characteristic of Coal and Rock Mass in Excavation from Crosscut Coal - Chengwu Li; Xiaoqian Zhang; Chengmin Wei; Yao Nie (Geofluids)
Coal and gas outburst is a serious disaster in the mining, and crosscut coal is the most prone to cause the coal and gas outburst. In order to study the mechanism of outburst, this paper studied the stress distribution characteristics in front of the working face in the process of rock roadway driving before implementing crosscut coal firstly. On this basis, the hypothesis of stress distribution on the “strong and soft face” of coal-rock mass was proposed. And by using the hypothesis, the mechanical equation for the parameter changes of the plastic zone in front of the working face in crosscut coal was established, and the width and morphological characteristics of the plastic zone in crosscut coal were analyzed. The results show that during the process, as the working face moves forward, the shape distribution of the plastic zone in front of the working face changes from the “semielliptical” to “semibutterfly,” And based on the distribution characteristics of plastic zone in working face in crosscut coal, modification proposals for outburst-prevention measures were proposed and provided technical support for the outburst-prevention measures and key parameters setting to prevent the coal outburst in crosscut coal.